An adaptive non-linear PDE-based speckle reduction technique for ultrasound images. (25th July 2011) - Srivastava, Rajeev; Gupta, J.R.P.; Parthasarathy, Harish; Srivastava, Subodh
In this paper, an adaptive nonlinear complex diffusion based filter is proposed to reduce the speckle noise from ultrasound images. The adaptive and modified version of a fourth order PDE is also proposed and examined for its suitability and efficacy for speckle reduction from ultrasound images. The performance of the proposed method is compared with constraint driven anisotropic diffusion based method, modified fourth order PDE based method and other methods such as Speckle Reducing Anisotropic Diffusion (SRAD) filter, Lee filter, Frost filter and Kuan filter in terms of various performance metrics such as Mean Square Error (MSE), Peak Signal-to-Noise Ratio (PSNR), Correlation Parameter (CP) and Mean Structure Similarity Index Map (MSSIM). The obtained results justify the applicability of the proposed scheme.